Integration of Artificial Intelligence in Learning at Madrasah Ibtidaiyah to Improve Students' Competence and Digital Literacy - Ainur Rofiq Hafsi (LP2M IAI Al-Khairat Pamekasan, 2026)
The integration of Artificial Intelligence in education has become a strategic innovation in responding to the demands of the digital era, particularly in enhancing students’ competencies and digital literacy. This study aims to analyze the implementation of Artificial Intelligence in learning at Madrasah Ibtidaiyah and its impact on improving students’ competencies and digital literacy.This research employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observations, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing.The findings reveal that the integration of Artificial Intelligence significantly improves students’ digital competencies, including their ability to use technology, access and evaluate information, and develop critical thinking skills. Furthermore, AI-based learning creates a more interactive, adaptive, and personalized learning environment, which enhances students’ motivation and engagement. However, the implementation still faces several challenges, such as limited technological infrastructure, varying levels of teachers’ digital competence, and the need for strengthening digital ethics literacy. The study concludes that the integration of Artificial Intelligence has strong potential to improve the quality of learning and prepare students with essential digital competencies. Therefore, continuous teacher training, institutional support, and effective policy frameworks are necessary to optimize the implementation of AI in education.